Production of single cell anode-supported SOFC using NiO/YSZ-YSZ-LSM/YSZ powder materials - ., Sulistyo (2015)
Solid oxide fuel cell (SOFC) is an energy conversion device that converts gas into electricity directly. The components consist of anode, electrolyte and cathode which have different properties and operate at high temperatures up to 1000 οC. SOFC requires a thin, robust, porous anode, dense electrolyte and porous cathode. Manufacturing of single cell using low compaction value and high diameter to thickness ratio is yet to be developed. The challenge of the higher diameter to thickness ratio is inhomogeneous density distribution which causes cracks during sintering. This research investigates the manufacturing of single cell using low compaction and high diameter to thickness ratio. The performance of single cell was evaluated using hydrogen and oxygen that are supplied to the anode and cathode respectively. Initially the anode was produced using ultrasonic (U/S) process and ball mill (BM) process. The materials for single cell are NiO/YSZ, YSZ, LSM/YSZ as anode, electrolyte and cathode, respectively. The cornstarch is used to create anode porosity while the material binder of the powder is polyvinyl alcohol (PVA) to increase green compact strength. The consolidation of anode was done using a low compaction load of 16 MPa with a diameter of 40 mm. The electrolyte and cathode layer were coated using wet powder spraying (WPS) technique. The sintering for single cell used a three step air sintering. The characterizations of the anode include porosity, permeability, bending strength, microstructure and these were tested to evaluate the performance of the single cell SOFC. The results demonstrated that the thin SOFC single cell was successfully obtained. The single cell SOFC has a thickness of 600 μm where the distribution of thickness for the anode, electrolyte, and cathode were 557.5 μm, 26.1 μm and 16.4 μm, respectively. The cell diameter obtained was 36 mm. The low compaction load and the diameter to thickness ratio were 16 MPa and 60, respectively. Performance of open circuit voltage (OCV) for U/S and BM process is 0.8 V and 0.66 V, respectively. Power density performance for U/S and BM process is 200.41mA/cm2 and 151.63mA/cm2 respectively. The results indicated that the performance of OCV and power density for U/S were 33.34% and 32.17 % higher than BM process.